Nanocomposites of polypropylene and polyethylene with montmorillonite type clays - Pawlak, A.; Morawiec, J.; Piorkowska, E.; Galeski, A. (Polimery, 2022)
General characteristics of polymeric nanocomposites containing montmorillonite (MMT) as well as the results of research concerning preparation and properties of nanocomposites with this filler, based on isotactic polypropylene (i-PP) or low density polyethylene (PE-LD) were presented. Structure, crystallization and mechanical properties of the nanocomposites were studied using X-ray diffraction, transmission electron microscopy, scanning electron microscopy, light microscopy, differential scanning calorimetry and tensile test. Blending conditions as well as type of a compatibilizer used (polypropylene grafted onto maleic anhydride or acrylic acid) significantly influence MMT exfoliation in i-PP matrix. MMT presence weakly influences i-PP crystallization at static conditions while causes intense spherulites nucleation under shear. Dependencies of tensile properties of nanocomposites based on i-PP matrix on MMT content and exfoliation degree (Figs 1-2) were investigated and interpreted. Polypropylene based nanocomposites exhibit increased elastic modulus while preserving accepted value of the elongation at break. Nanocomposites based on low density polyethylene exhibit high ability to plastic deformation. Films of compatibilized polyethylene nanocomposites were obtained using blow moulding technique and the effects of stretch and blowing degree on mechanical properties of the films (Table 1) were investigated.